2023
DOI: 10.3389/fnins.2023.1221579
|View full text |Cite
|
Sign up to set email alerts
|

Altered functional activity of the precuneus and superior temporal gyrus in patients with residual dizziness caused by benign paroxysmal positional vertigo

Cunxin Lin,
Dan Liu,
Yueji Liu
et al.

Abstract: ObjectiveBenign paroxysmal positional vertigo (BPPV) is a common clinical vertigo disease, and the most effective treatment for this disease is canal repositioning procedures (CRP). Most patients return to normal after a single treatment. However, some patients still experience residual dizziness (RD) after treatment, and this disease’s pathogenesis is currently unclear. The purpose of this study is to explore whether there are abnormal brain functional activities in patients with RD by using resting-state fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…The SMG is a key region identified in previous studies for vestibular information processing ( Lopez and Blanke, 2011 ; zu Eulenburg et al, 2012 ; Dieterich and Brandt, 2018 ). The functional and structural changes in SMG have been demonstrated in vestibular disorders like benign paroxysmal positional vertigo with residual dizziness, persistent postural-perceptual dizziness, and vestibular migraine ( Zhe et al, 2020 ; Lin et al, 2023 ; Maywald et al, 2023 ). A recent fMRI study has revealed decreased FC between the left lingual gyrus and the bilateral SMG in patients with AUVP ( Cheng et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The SMG is a key region identified in previous studies for vestibular information processing ( Lopez and Blanke, 2011 ; zu Eulenburg et al, 2012 ; Dieterich and Brandt, 2018 ). The functional and structural changes in SMG have been demonstrated in vestibular disorders like benign paroxysmal positional vertigo with residual dizziness, persistent postural-perceptual dizziness, and vestibular migraine ( Zhe et al, 2020 ; Lin et al, 2023 ; Maywald et al, 2023 ). A recent fMRI study has revealed decreased FC between the left lingual gyrus and the bilateral SMG in patients with AUVP ( Cheng et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%